Two pore channels control Ebolavirus host cell entry and are drug targets for disease treatment - Sakurai, Yasuteru (Science, 2015)
Ebolavirus causes sporadic outbreaks of lethal hemorrhagic fever in humans with no currently approved therapy. Cells take up Ebolavirus by macropinocytosis, followed by trafficking through endosomal vesicles. However, few factors controlling endosomal virus movement are known. Here we find that Ebolavirus entry into host cells requires the endosomal calcium channels called two pore channels (TPCs). Disrupting TPC function by gene knockout, small interfering RNAs or small molecule inhibitors halted virus trafficking and prevented infection. Tetrandrine, the most potent small molecule we tested, inhibited infection of human macrophages, the primary target of Ebolavirus in vivo, and also showed therapeutic efficacy in mice. Therefore, TPC proteins play a key role in Ebolavirus infection and may be effective targets for antiviral therapy.